Functionalized gold nanorod nanocomposite system to modulate differentiation of human mesenchymal stem cells into neural-like progenitors. Issue 1 (December 2017) - Alghazali, Karrer; Newby, Steven D.; Nima, Zeid; Hamzah, Rabab; Watanabe, Fumiya; Bourdo, Shawn; Masi, Thomas J.; Stephenson, Stacy M.; Anderson, David; Dhar, Madhu s.; Biris, Alexandru
Abstract A 2D multifunctional nanocomposite system of gold nanorods (AuNRs) was developed. Gold nanorods were functionalized via polyethylene glycol with a terminal amine, and, were characterized using transmission and scanning electron microscopy, ultra violet-visible and X-ray photoelectron spectroscopy, and Zeta-potential. The system was cytocompatible to and maintained the integrity of Schwann cells. The neurogenic potential of adipose tissue – derived human mesenchymal stem cells (hMSCs) was evaluatedin vitro . The expression pattern and localization of Vimentin confirmed the mesenchymal origin of cells and tracked morphological changes during differentiation. The expression patterns of S100β and glial fibrillary acidic protein (GFAP), were used as indicator for neural differentiation. Results suggested that this process was enhanced when the cells were seeded on the AuNRs compared to the tissue-culture surface. The present study indicates that the design and the surface properties of the AuNRs enhances neural differentiation of hMSCs and hence, would be beneficial for neural tissue engineering scaffolds.